Comparative analysis in real environment of trajectory controllers on ROS2 - Sant’Anna, Tiago B.; Argolo, Miguel B.; Lima, Rebeca T. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
This article presents a comparative analysis of three trajectory controllers - DWB, RPP, and MPPIC - implemented in Navigation2, a widely used navigation package in the ROS2 robotics platform. The aim is to assess the performance of these controllers in terms of trajectory time, distance traveled, motor effort, goal error, and computational resource consumption. Real-world scenarios were considered to evaluate their effectiveness and efficiency. The findings, highlighted in the article, yielded initial conclusions. In the first environment without obstacles, the DWB controller displayed superior performance, achieving the shortest time of 6.87 seconds, low effort, and the shortest distance covered. However, none of the controllers attained an exact desired pose. In the second environment, all controllers achieved a 100% success rate, with the MPPIC controller being the fastest at 9.66 seconds, requiring less effort and covering a shorter distance than the RPP controller. Overall, the MPPIC controller emerged as the most efficient, utilizing fewer computational resources while maintaining a high success rate.